The Significance of Microfinance Establishments on The Growth of Small to Medium Enterprises in Zimbabwe - Blessed Mveku; Tanaka. T. T. Mutero; T Nyamwanza; Munyaradzi Chagwesha; Peter Bhibhi (International Journal of Management, Entrepreneurship, Social Science and Humanities, 2023)
The study was conducted in the Midlands province of Zimbabwe, focusing on four towns: Kadoma, Kwekwe, Gweru, and Zvishavane. The study examines the establishment of microfinance institutions, which results in the growth of small to medium enterprises. Many SMEs in the Midlands province are finding it difficult to grow their business due to a lack of capital and the ability to access bank loans. The study aimed to determine the significance of microfinance establishments on the growth of small- to medium-sized enterprises in Zimbabwe. A descriptive research design was adopted. The study's sample size was 94 SME owners specialising in agriculture, mining, vending, groceries, beauty salons, auto repairs, transport services, and fast foods in the Midlands province. Data was analysed using Pearson correlation and simple linear regression. The study results showed a strong positive relationship between microfinance loans and Small to Medium Enterprise sales growth, as evidenced by a correlation coefficient 0.989. The results showed that microfinance loans positively affect the profitability of SMEs. The study also found that access to finance, competition, hyperinflation, and high taxes are the challenges affecting SMEs' firm size. The study shows several ways which can be done to improve the growth of SMEs, such as the extension of loan repayment tenure, review of lending policies, and lending SMEs higher packages for accomplishing their projects. The government should implement policies that find ways to reduce inflation, lower tax charges on SMEs, and draft policies that promote the development of SMEs in the country.